Adaptation of the cultural difference perceptions and intercultural sensitivity scale to the Kosovan culture: Validity and reliability analysis - Kervan, Enis; Morina, Shemsi; Kervan, Serdan (International Journal of Innovative Research and Scientific Studies, 2025)
This study aimed to adapt the Perceptions of Cultural Differences and Intercultural Sensitivity Scale to the cultural context of Kosovo. A total of 325 teachers from Turkish, Albanian, and Bosniak ethnic backgrounds participated. To evaluate the psychometric properties of the scale, Exploratory Factor Analysis (EFA), Confirmatory Factor Analysis (CFA), and reliability analyses were conducted. The results showed that the scale consists of 17 items grouped under three sub-dimensions: Self-Efficacy and Attitudes in Intercultural Interaction, Cultural Sensitivity and Openness, and Intercultural Communication Competence. CFA results strongly supported the three-factor structure. High factor loadings, low standard error values, and statistically significant Z-scores indicated that the scale has strong structural validity. Furthermore, the alignment of factor loadings with theoretical expectations and acceptable error levels demonstrated the psychometric robustness of the scale, which is especially important in multicultural contexts. As a recommendation, considering Kosovo's multicultural structure, future research should continue to explore intercultural sensitivity using diverse samples that include various ethnic backgrounds, socio-economic levels, and younger populations.